The effect of biological maturity status on ground reaction force production during sprinting - Colyer, S. L.; Nagahara, R.; Takei, Y.; Salo, A. I. T. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Sprint ability develops nonlinearly across childhood and adolescence. However, the underpinning ground reaction force (GRF) production is not fully understood. This study aimed to uncover the kinetic factors that explain these maturation-related sprint performance differences in Japanese boys and girls. A total of 153 untrained schoolchildren (80 boys, 73 girls) performed two 50-m maximal effort sprints over a 52-force-platform system embedded in an indoor track. Maturity offset (years from peak height velocity; PHV) was estimated using anthropometric data and used to categorise the children into six-year-long maturation groups (from group 1 [5.5-4.5 years before PHV] to group 6 [0.5 years before to 0.5 years after PHV). Maximum and mean step-averaged velocities across 26 steps were compared across consecutive maturation groups, with further GRF analysis (means and waveforms [statistical parametric mapping]) performed when velocity differences were observed. For boys, higher maximum velocities (effect size ± 90% CI = 1.63 ± 0.69) were observed in maturation group 2 (4.5-3.5 years before PHV) compared to group 1 (5.5-4.5 years before PHV), primarily attributable to higher antero-posterior GRFs across shorter ground contacts. Maximum velocities increased from maturation group 4 (2.5-1.5 years before PHV) to group 5 (1.5-0.5 years before PHV) in the girls (effect size ± 90% CI = 1.00 ± 0.78), due to longer ground contacts rather than higher GRFs per se. Waveform analyses revealed more effective reversal of braking forces and higher propulsive forces (e.g. 14%-77% of stance 4), particularly for comparisons involving boys, which suggested potentially enhanced stretch-shortening ability. Youth sport practitioners should consider these maturation-specific alterations when evaluating young athletes` sprint abilities.